5.4 W, 9.4 ns Pulse Width, Long-Wave Infrared ZGP OPO Pumped by Ho:YAG MOPA System - Chuan-Peng Qian; Ting Yu; Jing Liu; Yu-Yao Jiang; Si-Jie Wang; Xiang-Chun Shi; Xi-Sheng Ye; Wei-Biao Chen (IEEE Photonics Journal, 2021)
We demonstrated a narrow pulse-width long-wave infrared ZnGeP2 (ZGP) optical parametric oscillator (OPO) pumped by a 2.1 μm Ho:YAG master oscillator power-amplifier (MOPA). By short-cavity structure, a minimum pulse width of ∼12 ns was achieved at 1kHz, 2kHz and 3kHz in Ho:YAG oscillator. By employing a three-stage amplifier, a maximum average output power of 73.1 W with pulse width of ∼17 ns at the pulse repetition frequency of 3 kHz was obtained. Then a ZGP OPO pumped by the Ho:YAG MOPA was demonstrated. The maximum average output powers of 5.48 W at 8.2 μm and 22.4 W at 2.8 μm were obtained, corresponding to the pulse width of <10 ns.